Relationship between step-by-step foot kinematics and sprint performance - van den Tillaar, R. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of the study was to investigate the relationship between angular foot step-by-step kinematics and sprint performance during a 50 metre sprint in experienced male sprinters. Foot kinematics were measured using IMU devices integrated with a 3-axis gyroscope and a laser gun. The main findings were that maximal angular velocities increased until strides 6-7, where it stabilised. Time from touch down to dorsal flexion velocity was similar over all strides, whereas time from dorsal flexion velocity to toe off decreased until stride 6. Plantar flexion velocities, especially in toe off, showed the greatest associations with sprint times, whereas maximal dorsal flexion velocity presented no association with sprint times. Time from dorsal flexion velocity to toe off from stride 7 onwards determined the sprint performance and were shorter for faster sprinters.